Effects of growth hormone in the central nervous system - Frederick Wasinski; Renata Frazão; Jose Donato Jr (Archives of Endocrinology and Metabolism, 2020)
ABSTRACT Growth hormone (GH) is best known for its effect stimulating tissue and somatic growth through the regulation of cell division, regeneration and proliferation. However, GH-responsive neurons are spread over the entire central nervous system, suggesting that they have important roles in the brain. The objective of the present review is to summarize and discuss the potential physiological importance of GH action in the central nervous system. We provide evidence that GH signaling in the brain regulates the physiology of numerous functions such as cognition, behavior, neuroendocrine changes and metabolism. Data obtained from experimental animal models have shown that disruptions in GH signaling in specific neuronal populations can affect the reproductive axis and impair food intake during glucoprivic conditions, neuroendocrine adaptions during food restriction, and counter-regulatory responses to hypoglycemia, and they can modify gestational metabolic adaptions. Therefore, the brain is an important target tissue of GH, and changes in GH action in the central nervous system can explain some dysfunctions presented by individuals with excessive or deficient GH secretion. Furthermore, GH acts in specific neuronal populations during situations of metabolic stress to promote appropriate physiological adjustments that restore homeostasis. Arch Endocrinol Metab. 2019;63(6):549-56